Theoretical modalities of architectural communicability - Ciganović, Aleksa; Stevanović, Vladimir (Arhitektura i urbanizam, 2024)
The paper discusses the character of communication in the architectural profession. As architecture has a multidimensional discursive nature, architectural communicativeness is viewed as a complexly organized linguistic formation that is the result of the correlation and interaction of immanent technical discourse (an engineering, construction and design communication model) and communication models of other work environments, such as those which are normative-legal (an administrative and legislative communication model), scientific-academic (theoretical, critical, essay and translation models of communication) or journalistic (promotional and managerial models of communication). Within the mentioned subtypes of architectural communication, one can find polyphonic extralinguistic inclusions intertwined with discourses of other scientific and academic spheres. In this sense, the architectural code of communication is characterized not only by the functional terminology of tangent areas, but also by the picturesqueness of speech genres, based on the use of abstract and symbolic tropes, from personifications to metaphors. The basic assumption of the text is that the general differentiation of architectural communication – due to the apparent lack of methodological and theoretical material on the subject – can be initially consolidated through Berthelot's (Jean-Michel Berthelot) theory of socio-humanistic programmatic changes in the epistemology of the second half of the 20th century, which includes the periodization of naturalistic, intentional and symbolic epistemological polarity. In the light of the presented starting point, Berthelot's epistemological poles are understood at the communicative level – as communication poles, to be analyzed as complex, abstract and variant discursive patterns of changing relations to the categories of culture and nature, with the characteristics of cognitive, thematic, stylistic and structural unity.
Keywords: architectural communication; naturalistic discourse; intentional discourse; symbolistic discourse; Jean-Michel Berthelot